Implementasi Teknologi Artificial Intelligence dan Machine Learning dalam Praktik Akuntansi dan Audit: Sebuah Revolusi atau Evolusi - Judijanto, Loso; Al-Amin, Al-Amin; Nurhakim, Lukman (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
This research explores the implementation of Artificial Intelligence (AI) and Machine Learning (ML) technologies in accounting and auditing practices, focusing on whether it is a revolution or an evolution. With increasing data complexity and the need for faster analysis, AI and ML offer innovative solutions. These technologies can improve efficiency by speeding up the audit process, reducing human error, and detecting fraud more effectively. Literature and case studies show that the adoption of AI and ML in accounting has brought significant changes in the methodology and outcomes of audit work. While some see it as a revolutionary leap, others consider this development as a natural evolution of information technology in accounting. This research concludes that regardless of the viewpoint taken, AI and ML have and will continue to contribute to fundamental changes in the way accountants and auditors work, driving new standards in the accuracy, efficiency, and reliability of accounting and auditing work. The findings recommend the importance of investing in human resource training to maximize the benefits of these technologies.